Mega-influencer and celebrity brand engagement: antecedents and effect on fans’ purchasing behaviours - Zarkada, Anna K. (My University, 2023)
Since 2017 influencer marketing spend is reported to have grown exponentially but its growth rate is slowing down (Statista Research Department 2023) and lags behind that of traditional channels (The Business Research Company 2023) despite claims that influencer marketing is “the fastest-growing channel for brands” because “[i]nfluencers are trusted by millions of consumers” who “depend on influencer recommendations ” for their purchases (Digital Marketing Institute 2021). This paper puts the hype to the test and presents an in-depth in vivo investigation of actual consumer engagement with a celebrity Social Media Influencer (SMIs) and her product brands
Keywords: Social media marketing; Influencers; Social media influencers; Brand engagement; Consumer behaviour; Content